Two women and fencing - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a woman and a man with portable fencing rolled up in front of them. Behind them is a forklift, a u-haul trailer and equipment sitting on scaffolding at the National March on Washington for Lesbian and Gay Rights. The woman on the left wears a shirt that reads, "March on Washington, October 14, 1979.